2022
DOI: 10.1039/d1nj05283g
|View full text |Cite
|
Sign up to set email alerts
|

Copper deposited diatom-biosilica with enhanced photothermal and photodynamic performance for infected wound therapy

Abstract: Considering the increase in drug resistance due to the abuse of antibiotics, non-antibiotic strategies for the treatment of bacterial infections have the necessity and urgency. In this study, copper deposited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…The size of DBs varies basically from 5 to 9 μm, and rich attachment sites were provided for Cu metal mineralization and Ce nanoparticles. The organics in the diatom could be removed by a mixture of H 2 SO 4 and H 2 O 2 solution at 70 °C, leaving the inorganic residues composed of highly pure amorphous silica as DBs. The DBs exhibited a hierarchical porous structure with various pore sizes: the primary sector pore was ∼800 nm in length; the secondary circular pore was 30–50 nm in diameter; the tertiary circular pore was 1–2 nm in diameter. The doping of Cu into DBs was realized by a hydrothermal reaction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of DBs varies basically from 5 to 9 μm, and rich attachment sites were provided for Cu metal mineralization and Ce nanoparticles. The organics in the diatom could be removed by a mixture of H 2 SO 4 and H 2 O 2 solution at 70 °C, leaving the inorganic residues composed of highly pure amorphous silica as DBs. The DBs exhibited a hierarchical porous structure with various pore sizes: the primary sector pore was ∼800 nm in length; the secondary circular pore was 30–50 nm in diameter; the tertiary circular pore was 1–2 nm in diameter. The doping of Cu into DBs was realized by a hydrothermal reaction .…”
Section: Resultsmentioning
confidence: 99%
“…Our method is illustrated in Figure a. To improve the material stability and photocatalytic performance, DBs as a highly porous, light capture, and light absorbing natural silica material was used to prepare an n-type Cu-DBs semiconductor . Then, n-type CeO 2 -NPs were secondary mineralized on the surface of Cu-DBs to form a typical n–n semiconductor heterojunction.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, resulted in an improved sterilization effect and nearly 100% antibacterial efficiency against S. aureusand E. coli-infected wounds. In vivo experiments not only confirmed the antibacterial properties of the material, but also revealed that the same could fast track wound healing by inhibiting inflammation, promoting angiogenesis as well as collagen deposition, and modulating type-III to type-I collagen ratio [84]. Sherief et al used a similar approach, coating diatomite particles with AgNPs, and showed that the material is effective against five different pathogenic organisms [85].…”
Section: Antibiotics Deliverymentioning
confidence: 91%
“…Finally, Cong et al [84] and Sherief et al [85] have described the antimicrobial activity of metal-coated diatoms. These last two examples do not rigorously fall within the drug delivery category, but are illustrative of the tremendous versatility of diatom biosilica.…”
Section: Antibiotics Deliverymentioning
confidence: 99%
See 1 more Smart Citation